Acute Toxicity, Mutagenicity and Antimutagenicity of Ethanol Ocimum sanctum Leaf Extract Using Rat Bone Marrow Micronucleus Assay - Ekachai Khumphant,; Darunee Buripakdi Lawson, (Agriculture and Natural Resources, 2002)
Holy basil (Ocimum sanctum) is an herbal plant that is commonly used as an ingredient for cooking and as a medicinal plant. This plant is widely used in all Thailand regions for many food recipes. Previous studies have shown that Ocimum sanctum leaf extract (OE) possesses chemopreventive property against carcinogenesis and induction of the hepatic biotransformation enzyme profiles that are involved in detoxification of chemical mutagens. This study attempts to investigate the effect of an oral administration of OE on induction of toxicity, mutagenicity, and anti-mutagenicity using rat bone marrow micronucleus test. Cyclophosphamide was used to elucidate the possible mechanism of anti-mutagenicity property of this extract. OE was given daily via oral administration to Sprague-Dawley rats to determine; (1) acute toxicity, (2) mutagenicity, and (3) anti-mutagenicity against cyclophosphamide. The results shown that OE was not toxic up to the dose of 15 g/kg bw in 5-week-old rats. The mutagenicity, represented as micronucleus induction, was assessed by bone marrow using i.p. 80 mg/kg bw of cyclophosphamide 30 hours prior to bone marrow collection. Administration of OE at a dose 5 g/kg bw did not cause mutagenicity in the rats. On the other hand OE possesses the anti-mutagenicity activity resulting on the significant inhibition of micronucleus formation against cyclophosphamide after 7 and 21-day repeat oral administration of 5 g/kg bw of OE. The anti-mutagenicity of OE suggested an enhancement of detoxification enzymes against cyclophosphamide as shown in a reduction of micronucleus formation. It is possible that some compounds in OE may play an important role in such enhancement of detoxification mechanism. This study, therefore, confirmed health benefits of holy basil (Ocimum sanctum), especially grown in Thailand as an ingredient of food and as a medicinal plant to reduce mutagenicity.